Effectiveness of guidance and counselling policy and practice in rural Zimbabwean learners’ sustainable formation : a critical analysis - Munyaradzi, Chidarikire; Chikuvadze, Pinias; Dube, Sethule; Gonzo, Getrude (Penerbit Universiti Kebangsaan Malaysia, 2021)
In Zimbabwean secondary schools, the guidance and counselling policy and practice was brought in with the view to answer learners’ scholastic, societal and individual needs. However, the implementation of the policy and practice in teaching-learning activities for social sustainability was seen incomprehensible in light of numerous challenges, learners were going through. It is in this context that this paper sought to explore the extent to which a selected secondary school in one rural district in Zimbabwe was implementing the guidance and counselling policy and practice in its teaching-learning activities. A qualitative approach with specific reference to case study strategy was followed to acquire an in-depth comprehension of the issue under investigation in the selected secondary school in Lupane District, Matabeleland North Province. Literature method, critical policy analysis and in-depth interviews were used to generate data from ‘teacher-counsellors’ twenty who were purposively selected to take part in this study. Generated data was thematically analysed. From analysed data, it was noted that participants perceived the guidance and counselling activities as an important component for proper formation of conscientious inhabitants. However, it also surfaced from the discussion that various obstacles were obstructing the implementation of the policy and practice at a selected rural secondary school. Therefore, through the participants’ experiences in the learning activities, the guidance and counselling policy and practice was not being implemented fully for learners’ sustainable formation. We recommend that the secondary school’s stakeholders do consider guidance and counselling activities, an integral component of the learners’ learning activities to enhance their sustainable formation.